European citizenship as an instrument to protect vulnerability - Graça Enes (Oñati Socio-Legal Series)
The creation of European citizenship by the Maastricht Treaty was not enthusiastically received. The rights it conferred were essentially those already in force in the European Community. The case law of the ECJ gave substance to European citizenship, describing it as “the fundamental status of nationals of the Member States”. The interpretation of the ECJ shaped this new status and its rights, making it an instrument to protect migrant nationals of Member States, especially important for individuals in vulnerable situations: e.g. disabled people, homosexuals, even displaced students, welcoming in the judicial hermeneutic exercise a broad concept of vulnerability (Fineman 2010), whether structural and permanent, or individual or conjunctural; with regard to children, vulnerability justified the extension of protection to parents. The following analysis goes through some of the “leading cases” of Union citizenship, focusing on the protective scope of that status in the context of the concrete situation “sub judice”.